Integrasi Pemanfaatan Data Administrasi Kependudukan Dalam Rangka Mewujudkan Single Identity Number - Gery Runtu, Muhammad Rasdy (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2021)
The integration of population data and information implies the unification of population data and information in a system, the system in question is an application developed by the Ministry of Home Affairs for all Regency/City Population and Civil Registration Offices. With this integration, public service units are no longer problematic because this integration will create a population database where each resident only has one population data. The use of data and information held by the Population and Civil Registration Office of Parepare City has not been implemented properly, where each existing public service unit has its own database. The purpose of this paper is that the existing data and information can be utilized by all service units in Parepare. The methodology used is Observation, Interview and Literature Study. From the results of the research conducted, it is known that the utilization of population data and information through the Population Administration Information System Application has not been implemented in the form of cooperation in the use of SIAK data and information.